(untitled) (Nepalese Journal of Development and Rural Studies, 2017)
The existence of child labor is not a new phenomenon as children are still engaging in all the sector of employment. The objectives of the study was to assess economic status of school going domestic child workers (DCWs), to assess the root causes of DCWs and to examine present working condition of the DCWs. To the end, 50 DCWs studying in Santi Bidhya Griha Higher Secondary School of Kathmandu are selected as respondents. The finding shows that the cause of poverty is an essential factor to increase domestic child worker. DCWs are involving in low level households activities. Their working hour is higher than study period. Remuneration paid for DCWs is very low or not paid, behave of the owner towards DCW’s is low or medium in average. The bedding and fooding situations of the DCWs are not found good. Because of that most of them are not yet satisfied with their job but compelling to continue only for their school education life. At present 15 percent of the respondents are studying in primary level, 55 percent in lower secondary level and 30 percent in secondary level. Regarding job satisfaction, some of them want to kick out their job any time but some thoughtful children want to leave after completion of grade tenth. The thoughtful children want to start their professional career in teaching; business and political sectors and few of them also want to join police and army. However, they don’t have the knowledge of child labour act and child right. Nepalese Journal of Development and Rural Studies Vol. 14 (Joint issue) (1&2), 2017, Page:124-128